2013
DOI: 10.1186/1471-2296-14-26
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of New Zealand consumers perceptions of general practice nurses

Abstract: BackgroundAn important consideration in health service delivery is ensuring that services meet consumer needs and that consumers are satisfied with service delivery. Patient satisfaction can impact on compliance with suggested treatments and therefore impact on health outcomes. Comparatively few studies have explored consumer satisfaction with nurses in general practice.MethodsA sub-group of 18 consumers from a larger quantitative evaluation of consumer satisfaction with New Zealand general practice nurses par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 17 publications
4
42
0
2
Order By: Relevance
“…The current study generates important information to guide the development of the role of nurses working in general practice around their role in chronic disease management. This study confirms findings within the existing literature which demonstrate that health care consumers were generally satisfied with the chronic disease services delivered by the PN (Desborough et al, 2013;Halcomb et al, in press;Halcomb et al, 2013;Mahomed, 2012) However, unlike other studies of consumer satisfaction with PNs which have demonstrated variation in satisfaction as a result of demographic variables such as age (Cheraghi-Sohi et al, 2008;Halcomb et al, in press;Halcomb et al, 2011;Hall & Dornan, 1990), gender (Halcomb et al, in press), or ethnicity (Halcomb et al, in press;Halcomb et al, 2011), this study did not demonstrate a significant difference in either satisfaction or comfort related to demographic variables.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The current study generates important information to guide the development of the role of nurses working in general practice around their role in chronic disease management. This study confirms findings within the existing literature which demonstrate that health care consumers were generally satisfied with the chronic disease services delivered by the PN (Desborough et al, 2013;Halcomb et al, in press;Halcomb et al, 2013;Mahomed, 2012) However, unlike other studies of consumer satisfaction with PNs which have demonstrated variation in satisfaction as a result of demographic variables such as age (Cheraghi-Sohi et al, 2008;Halcomb et al, in press;Halcomb et al, 2011;Hall & Dornan, 1990), gender (Halcomb et al, in press), or ethnicity (Halcomb et al, in press;Halcomb et al, 2011), this study did not demonstrate a significant difference in either satisfaction or comfort related to demographic variables.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies indicate that consumers have little understanding of the knowledge level and scope of practice of nurses in general practice (Cheek et al, 2002;Halcomb et al, 2013;Hegney et al, 2004). Consumer attitudes reported in the literature value the nurses' role in general practice but still privilege the position of the general practitioner (Halcomb et al, in press;Patterson, Price, & Hegney, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the solutions to address the social determinants of men's health rely on the ability of the health professional workforce to recognise that men have significant potential to take an active role in their health (European Men's Health Forum 2009). A growing body of literature suggests that primary healthcare nurses (PHCNs) play a critical role in ensuring workforce supply and improving the quality of care and consumer experience (Cheek et al 2002, p. 6;Halcomb et al 2013), However, a review of the literature since 1994 found few published works that examine PHCNs meeting the needs of men in primary care or men's view of the PHCN role. The main aim of this qualitative study was to explore the perception of PHCNs in terms of men's health services; the second aim was to describe men's expectation of PHCNs.…”
Section: Introductionmentioning
confidence: 99%